Strategic Tourism Planning and its Influence on the Organizational Performance of Tourism Organizations - A Study of a Sample of Tourism and Travel Companies in the Holy Najaf Governorate - Al-Khalidy, Dr. Adel Turki; Madloul Al-Janabi, Karrar Muhammad; Keshwan, Abdulmohsin Jawad (Research Parks Publishers, 2023)
The purpose of this study is to determine the extent to which strategic tourism planning contributes to the improvement of organizational performance in the district that was studied. In order to investigate the nature of the relationship that exists between the variables that were covered in the study, the descriptive-analytical method was utilized. The questionnaire served as the primary instrument for the purpose of data collection. (325) questionnaires were distributed to a random sample of The employees are employees of (10) tourism and travel companies in the Al-Najaf Governorate (Al-Kamal Company, Jannat Al-Najaf Company, Al-Hikma Company, Al-Dhikra Company, Al-Qassim Company, Al-Mustafa Company, Al-Bashir Company, Al-Marbad Company, Al-Salwan Company, Horizon Road Police), and the number of questionnaires was (285) questionnaires were retrieved, a total of 282 were considered valid for statistical analysis, and the percentage of those who responded was 86.8%. For the purpose of analyzing the practical component of the study, the researcher made use of a wide variety of statistical tools and methods. These included the arithmetic mean, the standard deviation, the coefficient of variation, the relative importance, the correlation coefficient, and the simple regression approach. In addition to Excel (2007), complex statistical applications such as AMOS.V.25 and SPSS.V.26 were utilized in order to conduct the analysis. Based on the findings of the theoretical research, it was discovered that there is a vacuum in understanding on the role that strategic tourism planning plays in improving organizational performance in general, and in particular in the companies that were investigated. In terms of the practical findings of the research, it was found that there was a significant and direct correlation between tourist strategic planning in its dimensions and organizational performance, as well as a significant and negative influence relationship between the two. Through the findings of the investigation, the researchers were able to arrive at a number of conclusions that demonstrated the correctness of the majority of their hypotheses. According to the findings of the study, it is recommended that the tourism and travel companies that were surveyed in the Al-Najaf Governorate be encouraged to develop a current vision that guarantees their continued existence and survival in a manner that is proportionate and adapted to the environment in which they operate, as well as their capacity to absorb and contain the changes that occur within them. The presence of this environment helps to improve the performance of the overall organization.